Analisis Kontribusi Perbankan Syariah Terhadap Pertumbuhan Ekonomi Indonesia - Eva Sofariah; Fatmi Hadiani; Dadang Hermawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
The purpose of this study was to determine the effect of the dependent variables of Total Assets, Third Party Funds, Financing (mudharabah, musyarakah, murabahah), and ZISWAF on Indonesia's Economic Growth represented by GDP as dependent variable. The data used is financial reports for the 1st quarter of 2017 to the 4th quarter of 2020 sourced from Islamic Commercial Banks, Sharia Business Units, the Central Statistics Agency, and the Financial Services Authority. The method used is Autoregressive Distributed Lag (ARDL) to see the long-term and short-term effects of the independent variable on the dependent variable. The results of the study show that Total Assets and ZISWAF have a significant positive effect in the long and short term on GDP. Third Party Funds have a significant long-term and short-term negative effect on GDP. Financing has a significant positive effect in the long term but in the short term has a significant negative effect on GDP. In addition, simultaneously all independent variables have a significant positive effect on GDP.